Customer’s satisfaction measurement using cognitive and emotion judgment survey: a case study of INTEC / Zolidah Kasiran - Kasiran, Zolidah (Institute of Graduate Studies, UiTM, 2012)
Customer satisfaction is very important to organization in order to keep the customer loyal to the company. The research of customer satisfaction have been focusing on the cognitive judgment theory where the feedback collected from the customer was rely on the recalling the experiences. This method of cognitive judgment in measuring customer satisfaction have a problem that customers tend to rate customer satisfaction survey highly, as the cognitive judgment theory rely on remembering of the experience. The objective of this study is to propose a model to produce a clean input dataset for neural network classifier, to propose customer satisfaction model that combining the cognitive judgment and emotion judgment theories to balance the customer satisfaction rate. Another objective is to construct and conduct the satisfaction model based on the case study done at INTEC and to verify and confirm the reliability of the customer satisfaction model.